PENGARUH METODE PEMBELAJARAN BERBASIS MASALAH TERHADAP PEMAHAMAN KONSEP PENDIDIKAN AGAMA ISLAM PADA SISWA SMP YAMAMA - Wahyu Adithya; Erik Novianto; Willy Radinal (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
The research investigates the impact of Problem-Based Learning (PBL) method on the understanding of Islamic Religious Education (IRE) concepts among junior high school students. The study aims to determine whether the implementation of PBL enhances students' comprehension of IRE concepts compared to conventional teaching methods. The research involved a quasi-experimental design with two groups: an experimental group receiving PBL and a control group receiving traditional teaching. Data was collected through pre-test and post-test assessments measuring students' understanding of IRE concepts. Additionally, qualitative data was gathered through interviews to gain insights into the experiences of both students and teachers with the PBL method. The findings revealed a significant improvement in the understanding of IRE concepts among students in the experimental group compared to those in the control group. Factors influencing the effectiveness of PBL implementation, including teacher readiness, school support, student motivation and engagement, and adaptation to students' characteristics and local contexts, were identified. The study underscores the complexity of implementing PBL in the context of IRE education in junior high schools. It emphasizes the need for strong support from various stakeholders, including teachers, schools, and students, as well as appropriate adjustments to enhance its effectiveness. The research contributes to the understanding of innovative teaching methods in IRE education and provides practical implications for educators and policymakers to improve the quality of religious education in junior high schools.